Angiostrongylus vasorum in the eye: new case reports and a review of the literature. Issue 1 (December 2016) - Colella, Vito; Lia, Riccardo; Premont, Johana; Gilmore, Paul; Cervone, Mario; Latrofa, Maria; D'Anna, Nunzio; Williams, Diana; Otranto, Domenico
Abstract Background Nematodes of the genusAngiostrongylus are important causes of potentially life-threatening diseases in several animal species and humans.Angiostrongylus vasorum affects the right ventricle of the heart and the pulmonary arteries in dogs, red foxes and other carnivores. The diagnosis of canine angiostrongylosis may be challenging due to the wide spectrum of clinical signs. Ocular manifestations have been seldom reported but have serious implications for patients. Methods The clinical history of three cases of infection withA. vasorum in dogs diagnosed in UK, France and Italy, was obtained from clinical records provided by the veterinary surgeons along with information on the diagnostic procedures and treatment. Nematodes collected from the eyes of infected dogs were morphologically identified to the species level and molecularly analysed by the amplification of the nuclear 18S rRNA gene. Results On admission, the dogs were presented with various degrees of ocular discomfort and hyphema because of the presence of a motile object in the eye. The three patients had ocular surgery during which nematodes were removed and subsequently morphologically and molecularly identified as two adult males and one female ofA. vasorum . Conclusions Three new cases of canine ocular angiostrongylosis are reported along with a review of other published clinical cases to improve the diagnosis and provide clinical recommendation for this parasitic condition. In addition, the significance of migratory patterns of larvae inside the host body is discussed. Veterinary healthcare workers should include canine angiostrongylosis in the differential diagnosis of ocular diseases.